Resilience, complexity and digital transformation: Three case studies in the valves industry - Codara, L.; Sgobbi, F. (Journal of Manufacturing Technology Management, 2023)
Purpose This paper shows how the interplay between organisational resilience and environmental complexity justifies the existence of differentiated yet successful approaches to digital transformation. Design/methodology/approach A multi-case method is applied to test our research hypotheses by contrasting the digital transformation of three Italian companies in the valves industry. Findings Different combinations of technological and organisational tools, hence diversified digital transformations, can be successful, provided that they are supported by a coherent set of resilience factors and allow for the implementation of strategic approaches aligned with the resilience capacity of the firm. Practical implications Awareness that resilience capacity shapes digital transformation and the strategies available to engage with external complexity should focus managers to invest in the alignment and the reinforcement of the factors underlying organisational resilience. Originality/value Most literature so far focused on the antecedents to digital transformation. In contrast, this paper focuses on the transformation process and highlights how the resilience capacity of the firm affects the unfolding of digital transformation and the emergence of diversified yet successful paths. In addition, in contrast with a dichotomous approach to external complexity this paper shows that digital transformation involves a mix of complexity reduction and complexity absorption strategies.